Podcast Training in the Field of Malay Literature and Culture Through the Empowerment of the Riau Literary Community - Roziah, Roziah; Arianto, Jok; Hermaliza, Hermaliza; Piliang, Wilda Srihastuty Handayani; Nurhidayah, Nurhidayah; Nurisra, Hafara; Rahmadani, Annisa; Huda, Nurul (Widyagogik, 2025)
The purpose of this activity is to increase the capacity of media literacy and community broadcasting skills through podcast training in the field of Malay literature and culture. This PkM is carried out through the empowerment of the Riau Literary Community as the main partner in the preservation and dissemination of Riau Malay culture. This activity, which is funded by the Islamic University of Riau, is carried out in stages. The implementation method includes socialization, training in writing cultural news scripts, vocal and broadcasting techniques, and live podcast production practices. The results of the activity showed that participants were able to produce 20 news manuscripts that raised the theme of Riau Malay literature and culture. In addition, participants also managed to produce 20 podcast broadcasting videos as the output of the activity. This activity not only improves the technical skills of participants in the production of digital content, but also encourages the active role of the community in the preservation and dissemination of Malay cultural values through digital media. Thus, this service activity contributes to strengthening the capacity of the literary community as an agent of cultural preservation that is adaptive to the development of information technology.